Networks of highly branched stigmarian rootlets developed on the first giant trees - Hetherington, A; Berry, C; Dolan, L (National Academy of Sciences, 2016)
Lycophyte trees, up to 50 m in height, were the tallest in the Carboniferous coal swamp forests. The similarity in their shoot and root morphology led to the hypothesis that their rooting (stigmarian) systems were modified leafy shoot systems, distinct from the roots of all other plants. Each consists of a branching main axis covered on all sides by lateral structures in a phyllotactic arrangement; unbranched microphylls developed from shoot axes, and largely unbranched stigmarian rootlets developed from rhizomorphs axes. Here, we reexamined the morphology of extinct stigmarian systems preserved as compression fossils and in coal balls from the Carboniferous period. Contrary to the long-standing view of stigmarian systems, where shoot-like rhizomorph axes developed largely unbranched, root-hairless rootlets, here we report that stigmarian rootlets were highly branched, developed at a density of ∼25,600 terminal rootlets per meter of rhizomorph, and were covered in root hairs. Furthermore, we show that this architecture is conserved among their only extant relatives, herbaceous plants in the Isoetes genus. Therefore, despite the difference in stature and the time that has elapsed, we conclude that both extant and extinct rhizomorphic lycopsids have the same rootlet system architecture.